Implantação da política antimanicomial do poder judiciário no Ceará: um estudo avaliativo a partir da desinstitucionalização do manicômio judiciário cearense - Diniz, David dos Anjos (2025)
The Psychiatric Reform Movement, embodied through Law No. 10,216/2001, has been in dispute and in the process of consolidation for decades. It remains a battle that continues to follow a complex path toward full implementation. Individuals with mental disorders who are in conflict with the law have historically been subject to silencing, segregation, and invisibility. Brazil has a long history of systematic violations of their rights, particularly through the institutionalization of such individuals in Judicial Asylums. The Anti-Asylum Policy of the Judiciary, established by Resolution No. 487/2023 of the National Council of Justice (CNJ), emerges in this context as a response to this reality, aiming to bring about anti-asylum transformation through care and treatment in freedom, in alignment with deinstitutionalization processes. The general objective of this study is to evaluate the implementation of the Judiciary9s Anti-Asylum Policy, based on the deinstitutionalization of the Judicial Asylum in Ceará. The specific objectives are: to identify the guiding principles of the policy concerning the field of Mental Health, the Psychiatric Reform, and its interfaces with the Psychosocial Care Network; to historically and conceptually understand Judicial Asylums in Brazil; to characterize the paradigms of the relationship between Mental Health and the Justice System; to present the Anti-Asylum Policy of the Judiciary, contextualizing the scenario in Ceará; and to illustrate the process of deinstitutionalization of the Judicial Asylum in Ceará. The study adopts the theoretical and methodological perspective of in-depth evaluation. It is a qualitative research study. The objectives were pursued through bibliographic and documentary research, analyzing official documents and regulatory instruments, as well as drawing on the author's personal experiences through consultation of his notes journal. The findings indicate that the implementation of the Judiciary9s Anti-Asylum Policy faces significant challenges, particularly in changing institutional culture, strengthening public policies, and fostering inter-institutional dialogue. Nevertheless, its implementation has proven to be feasible through strategic actions, inter-institutional collaboration, and a commitment to and sensitivity toward the issue, all aimed at ensuring rights.